Addition of Glycerol as A Growth Stabilizer for Trichoderma asperellum in Bran-Based Growth Media - Chahyunisa, Alifia; Anhar, Azwir (Jurnal Biologi Tropis, 2025)
Biofertilizer is a fertilizer that contains microorganisms that increase plant fertility and reduce environmental pollution. One of the microorganisms that can be used as a biofertilizer is Trichoderma asperellum. Trichoderma can be cultured in several growth media, one of which is bran. In an effort to extend the shelf life of Trichoderma, glycerol is added as a stabilizer.This research aims to see how the addition of glycerol affects the shelf life of Trichoderma asperellum. This reserach is experimental research. Data were analyzed  using a completely randomized design (RAL). The treatment given in this research was by adding glycerol to the T. asperellum growth medium. T. asperellum cultures which were cultured in liquid bran-based media which were given glycerol and which not given glycerol were observed for spore growth, then the spore density was counted using a haemocytometer every 15 days. The research results obtained were that T. asperellum was able to survive in the growth medium for 45 days and had no real effect because it was unable to maintain the number of T. asperellum spores.